The Maintenance of Sindang Beliti Dialect in Muara Beliti, South Sumatera - Yenni Anggraini; Ida Zuraida (Universitas Widyatama, 2020)
Cultural heritage is an object or intangible attribute which is an identity of a society inherited from previous generations, which is preserved for generations to come. Cultural heritage contains not only an objects but also an intangible object such as languages, dialects, and rituals. One of Intangible culture is Sindang Beliti dialect which is from South Sumatera Province. Sindang Beliti dialect included in the Austronesian language used by Sindang tribes which is Lembak, Lembak delapan, and Muara Beliti. This study aimed to determine causal factors of sindang beliti dialect was shifted, and find out what were efforts to maintain the dialect. This study used quantitative-method which data collected by distributing questionnaires to 30 respondents included people, linguists, and Musi Rawas district government. Theory used in this study are from Holmes (2001) and Fishman (1972). The results of this study indicated that there were 3 casual factors of sindang beliti dialect was shifted. They were social, demographic, and legal factors. There were also found 5 efforts to maintain sindang beliti dialect included holding regional song competitions in every anniversary celebration of Musi Rawas district, producing radio broadcasts used sindang beliti dialect, building a playground with the name taken from sindang beliti dialect which is